VOCAL LEARNING FOR EIGHTH GRADE STUDENT IN 281 JAKARTA JUNIOR HIGH SCHOOL BY LEARNING IN PERSON - Keffa Ellena, Ken; Ikasari Ichwan, Clemy; Supriadi, Didin (Jurnal Penelitian Musik, 2023)
The learning process in Indonesia has been disrupted due to the COVID-19 pandemic. Class VIII vocal learning at SMPN 281 Jakarta, which initially had to meet face-to-face, required teachers and students to continue learning at home by doing online. Of course, after carrying out online learning, you need to re-adjust to face-to-face learning. Online learning is also a bit difficult to do if the material being studied is in the form of a practicum. Like one of them is vocal learning. In this learning, it is certain that the things that are taught are in the form of practice or are carried out directly. The purpose of this study is to find out how the vocal learning process in the school is through face-to-face after conducting an online learning. This study uses a qualitative approach to generate data in the form of descriptive text. The author also uses three research instrument techniques, including observation, interviews, and documentation. From the results of the study it is known that; Vocal learning for class VIII at SMPN 281 Jakarta was found in the same learning steps as the steps in the Project Based Learning learning model. This can be proven by the existence of work project planning, preparation of activity schedules, project monitoring, as well as assessment and evaluation of student work project results. In addition, it was also found that vocal techniques were still used in vocal learning which were taught and trained in the class